2023
DOI: 10.1111/jcmm.17788
|View full text |Cite
|
Sign up to set email alerts
|

Scutellarin inhibits the glioma cell proliferation by downregulating BIRC5 to promote cell apoptosis

Abstract: Glioma is considered as the most common primary tumour in the adult brain, with the highest degree of malignancy; among glioma types, glioblastoma is the most invasive and lethal. 1,2 Although multinational treatment strategies have improved in the past few decades, the prognosis of patients with glioma remains unfavourable. 3,4 In particular, the median survival time of patients with high-grade malignant glioma is ≤14 months. 5,6 And the 5-year survival rate of glioblastoma patients is <3%. 7 Therefore, there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Wang et al [ 56 ] found that scutellarin was able to inhibit the growth of glioma, as well as the proliferation and migration of glioma cells. In addition, scutellarin could significantly reduce the expression of baculovirus inhibitor of apoptosis protein 5 (BIRC5), thereby reversing the inhibition of apoptosis in glioma cells and exerting its anti-glioma effect.…”
Section: Pharmacological Effectsmentioning
confidence: 99%
“…Wang et al [ 56 ] found that scutellarin was able to inhibit the growth of glioma, as well as the proliferation and migration of glioma cells. In addition, scutellarin could significantly reduce the expression of baculovirus inhibitor of apoptosis protein 5 (BIRC5), thereby reversing the inhibition of apoptosis in glioma cells and exerting its anti-glioma effect.…”
Section: Pharmacological Effectsmentioning
confidence: 99%